2005
DOI: 10.1063/1.2056591
|View full text |Cite
|
Sign up to set email alerts
|

On the lack of thermal percolation in carbon nanotube composites

Abstract: Recent experiments demonstrated very low percolation thresholds for carbon nanotube composites signified by steep increases in electrical conductivity at very low nanotube loadings. By contrast, thermal transport measurements, even on the same samples, showed no signature of the percolation threshold. These contrasting behaviors are particularly intriguing considering that both transport processes are described by the same continuum equation. In this letter we present a theoretical analysis based on finite ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
163
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(173 citation statements)
references
References 13 publications
(13 reference statements)
7
163
3
Order By: Relevance
“…9,21 The absence of a significant increase in thermal conductivity at low loadings is attributed to the modest difference of the constituent thermal conductivities and the large interfacial thermal resistance between the polymer matrix and SWNT, as previously described. 11,22 Weak thermal coupling between the SWNT and polymers causes large interfacial thermal resistance.…”
Section: Resultsmentioning
confidence: 99%
“…9,21 The absence of a significant increase in thermal conductivity at low loadings is attributed to the modest difference of the constituent thermal conductivities and the large interfacial thermal resistance between the polymer matrix and SWNT, as previously described. 11,22 Weak thermal coupling between the SWNT and polymers causes large interfacial thermal resistance.…”
Section: Resultsmentioning
confidence: 99%
“…The large TBR at CNT/matrix interface can be attributed to the fundamental property -high Kapitza resistance [18] between one-dimensional (1D) CNTs and 3D bulk owing to the large difference in the phonon density of states (DOS). It was also suggested that the lack of thermal percolation in CNT composites can negatively affect their heat conduction properties [19]. Interestingly, the electrical percolation thresholds f T for CNT composites are very low, f~0.1 vol.…”
Section: Figurementioning
confidence: 99%
“…Presence of adsorbed polymer layers around the fillers prevent the formation of percolation network and filler-filler phonon transfer. Even if the fillers are in direct contact with each other, due to their [292] small contact area, the matrix and its interfacial resistance play a key role in heat transfer [272].…”
Section: Thermal Conductivitymentioning
confidence: 99%